Breastfeeding practice in Bosnia and Herzegovina - Darinka Šumanović-Glamuzina (Hygeia Press di Corridori Marinella, 2013)
Bosnia and Herzegovina is one of the new countries established after the break up of the former Yugoslavia. One of the unfortunate legacies of this country due to the 1992-1994 war is the destruction of human and material resources. Despite many negative events, steady progress can be seen in social, technological and cultural aspects of life. According to the global public health recommendation, infants should be breastfed for the first six months of life to achieve optimal growth, health and development. Therefore, to meet their evolving nutritional requirements, infants should receive nutritionally adequate and safe food, with Breastfeeding (BF) extended up to and beyond two years of age. In Bosnia and Herzegovina (B&H) majority of mothers (estimated at 95%) have initiated breastfeeding. However, Exclusive Breastfeeding (EBF) is not commonly practiced, and BF ceases by the age of five months. After 1995, a number of programs were introduced by WHO and UNICEF in B&H with a primary goal to ensure that babies were given a healthy start in life. Through implementation of Baby-Friendly Hospital Initiative (BFHI), enabling exact public health survey - the Multiple Indicator Cluster Survey (MICS), it would be possible to create comparable health indicators and make a step forward to promote and support breastfeeding practice as the best option for infants.